Polyphenols Inhibit Candida albicans and Streptococcus mutans Biofilm Formation - Yosi Farkash; Mark Feldman; Isaac Ginsburg; Doron Steinberg; Miriam Shalish (MDPI AG, 2019)
Background: Streptococcus mutans (S. mutans) and Candida albicans (C. albicans) are two major contributors to dental caries. They have a symbiotic relationship, allowing them to create an enhanced biofilm. Our goal was to examine whether two natural polyphenols (Padma hepaten (PH) and a polyphenol extraction from green tea (PPFGT)) could inhibit the caries-inducing properties of S. mutans and C. albicans. Methods: Co-species biofilms of S. mutans and C. albicans were grown in the presence of PH and PPFGT. Biofilm formation was tested spectrophotometrically. Exopolysaccharides (EPS) secretion was quantified using confocal scanning laser microscopy. Biofilm development was also tested on orthodontic surfaces (Essix) to assess biofilm inhibition ability on such an orthodontic appliance. Results: PPFGT and PH dose-dependently inhibited biofilm formation without affecting the planktonic growth. We found a significant reduction in biofilm total biomass using 0.625 mg/mL PPFGT and 0.16 mg/mL PH. A concentration of 0.31 mg/mL PPFGT and 0.16 mg/mL PH inhibited the total cell growth by 54% and EPS secretion by 81%. A reduction in biofilm formation and EPS secretion was also observed on orthodontic PVC surfaces. Conclusions: The polyphenolic extractions PPFGT and PH have an inhibitory effect on S. mutans and C. albicans biofilm formation and EPS secretion.